Health Risks of Overweight and Obesity - An Over View - Afridi, Aien Khan; Khattak, Muhammad Muzaffar Ali Khan; Safdar, Mahfara; Khan, Alam (Asian Network for Scientific Information, 2003)
Obesity is a risk factor for the development of various diseases like CHD, hypertension, stroke, NIDDM, osteoarthritis, sleep apnea and cancers of endometrium, breast, prostrate and colon. Psychological consequences of obesity range from lowered self-esteem to clinical depression. Many of these conditions are revisable through weight loss and maintenance. Weight reduction may be life saving so it is necessary to reduce weight.